Primary care physicians’ perceptions of hypertension management in Qatar: A qualitative study using the theoretical domains framework - Nada Abdelkader; Ahmed Awaisu; Hazem Elewa; Samya Ahmad Al Abdulla; Maguy Saffouh El Hajj (PLoS ONE, 2025)
Antihypertensive medications are known to reduce the incidence of hypertension complications. While the benefits of these medications are recognized, the factors influencing the prescribing practices of primary care physicians in Qatar have not been assessed. This study investigated Qatar primary care physicians’ experiences, practices, and perceptions regarding hypertension management. The study further evaluated the factors that influence their prescribing behaviors and identified strategies for improving hypertension management in primary healthcare settings. A qualitative case study was conducted through one-to-one semi-structured interviews with physicians practicing at the 31 Primary Health Care Corporation (PHCC) centers in Qatar. Due to the small population size, there was no need for sample size calculation and whole population sampling was used (N=179). Physician leads at each PHCC center helped identify eligible participants. Study information were shared via email and interested candidates were contacted to arrange for interviews at their convenience. The interview guide questions were designed based on the 14 domains of the Theoretical Domains Framework (TDF) of behavior change. Interviews were conducted virtually and transcribed verbatim. Thematic analysis was undertaken using inductive and deductive approaches. Twelve themes emerged, including physicians’ knowledge, skills, goals and role in hypertension management, confidence about prescribing decisions, optimism that prescriptions yield positive results, methods to ensure the appropriateness of prescriptions, emotions, and experiences when prescribing antihypertensives, perceived barriers, and facilitators when prescribing and social influences. Strategies for improving hypertension management were also suggested. In conclusion, multiple factors were identified that affect participants’ antihypertensive prescribing. Further research is needed to evaluate the suggested strategies’ effectiveness and to explore other improvements.